Atomic habits : tiny changes, remarkable results : an easy & proven way to build good habits & break bad ones - Clear, James (London: Cornerstone press, 2018)
James Clear, an expert on habit formation, reveals practical strategies that will teach you how to form good habits, break bad ones, and master the tiny behaviors that lead to remarkable results. He draws on proven ideas from biology, psychology, and neuroscience to create an easy-to-understand guide for making good habits inevitable and bad habits impossible.
Includes bibliographical references (page 273-298) and index.
Keywords: Habit; Habit breaking; Behavior modification; BUSINESS & ECONOMICS / Organizational Behavior; PSYCHOLOGY / Social Psychology; SELF-HELP / Personal Growth / General; Behavior modification; Habit; Habit breaking; Nonfiction; Self-help publications; Self-help publications